PSYCHOLOGICAL STUDY OF LITERATURE ON THE MAIN CHARACTER OF THE PLAY “BULAN BUJUR SANGKAR” BY IWAN SIMATUPANG - Titin Rostini; Angelina Sepiani Kusmawati; Resti Febrisanti; Adita Widara Putra (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research aims to describe the psychological character of parents in the play “Bulan Bujur Sangkar” by Iwan Simatupang by using psychological studies of the characters contained in the play. The method used in this research is descriptive and literature review. This process involves collecting data through analyzing relevant documents. Literary works are artistic expressions that not only reveal stories and characters, but also reflect various aspects of human life such as emotions, conflicts, and thoughts. Literature can capture the complexity of human psychology through stories and symbols and provide deep insight into a person's mental and emotional state. The descriptive method in this study was used to collect data related to the research topic. This process involves collecting data through analyzing relevant documents. In the literature review, this research refers to relevant theories and previous studies that have similar topics or methodologies. The results of this study show the absurdity of parental characters through three stages of thinking concepts namely Id, Ego, and Supergo. In the play Bulan Bujur Sangkar, the parent character fights back by committing suicide on the gallows.